KEABSAHAN ENGRAILED-2 DI KANKER PROSTAT - Elsa Yulius; Ida Parwati; Anna Tjandrawati; Dewi Kartika T (Indonesian Association of Clinical Pathologist and Medical laboratory, 2014)
Prostate cancer is one of the most common malignancy of males found worldwide including in Asia, and is the second most commoncause of male death in Western countries. Specific cause of prostate cancer is not yet elucidated, but there are several risk factors as well.The diagnosis of prostate cancer is confirmed by digital rectal examination (DRE), prostate-specific antigen (PSA), and a biopsy withtrans-rectal ultrasonography (TRUS). However, the sensitivity of DRE and PSA examinations are low and not good enough to detectprostate cancer. Currently there is a new test called Engrailed-2 (EN2) examination with enzyme-linked immunosorbent assay (ELISA)micro method. The test is simple and uninvasive one. This study is aimed to know the validity of urinary EN2 protein level measurementto detect prostate cancer by analysing. This study was conducted at Dr. Hasan Sadikin Hospital Bandung between November 2012 untilMarch 2013. This study was a diagnostic test with cross sectional design. The subjects of study were men whom suspected to have prostatecancer by DRE, PSA value (≥4 ng/mL) and TRUS biopsy. Urinary EN2 protein levels were measured using ELISA micro method. Statisticalanalysis used Mann-Whitney test, table 2×2 and ROC curve. In this study there are 50 subjects, where the result of positive biopsy forprostate cancer were found on 17 subjects and the negative were on 33 subjects. The study results on cut off value of >0.7 ng/mL gavethe sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of 94.12%, 63.64%, 57.1%, 95.5% and 74%,respectively. In conclusion of this study, that the urinary EN2 protein level examination using ELISA micro method has the high sensitivityand moderate specificity, thus these procedure primarily can be used for the screening of prostate cancer.